Value chain analysis of smallholder milk producer in West Hararghe Zone, Ethiopia - Azeb Lemma Kebede Adune Dinku; Mohammed Sheko (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
The study was aimed at analyzing milk value chains in West Hararghe zone with 140 producers were randomly selected from list of dairy producer kebeles. Meanwhile, 30 traders from different markets and 30 consumers in Chiro, Bedessa Gemechis and Mieso towns were selected and interviewed. Heckman two stage models were applied to identify determinants of milk market participation and volume of milk supply to the market. The results shows among those variables hypothesized to affect milk market participation decision, distance to the nearest market, crop income and age of household head  were negatively and significantly affecting participation decision and also livestock unit is affect participation decision significantly and positively. Land size, improved dairy cows, livestock unit were significantly and positively influencing the value of milk marketed. The value chain analysis revealed that the major value chain actors are input suppliers, producers, collectors, rural and urban wholesalers, retailers, cafes and consumers. It is also found that milk passes through several intermediaries with value added products (boiled milk and yoghurt) before reaching the ultimate users. Therefore, policies aiming at increasing producer's provision of modern inputs, number of milk cows and improving livestock production of milk cows and change of their attitudes towards milk production and processing, participating to dairy market were recommended to accelerate milk value chains development in the study area.